Динамические характеристики главных электроприводов прокатных станов с синхронными двигателями с учетом их взаимного влияния через прокатываемый металл - Кузнецов, Борис Иванович; Никитина, Татьяна Борисовна; Коломиец, Валерий Витальевич; Бовдуй, Игорь Валентинович; Волошко, Александр Валерьевич; Виниченко, Елена Владимировна (НТУ "ХПИ", 2010)
The mathematical model of rolling mills main drives with synchronous motor as a twomass electromechanics system for a short line and as a three-mass electromechanics system for a long line with friction nonlinear moments and with influence of rental rollers on each other during rolling through the rolled metal is developed. The example of dynamic characteristics for such model is given.
Dynamic characteristics of rolling mills main drives with synchronous motor with influence of rental rollers on each other
Keywords: модель математическая; система электромеханическая; момент упругости; скорость вращения; редуктор